Social Accounting Matrix Kenya - CGIAR (CGIAR System Organization, 2023)
The Kenya 2021 SAM was jointly developed by Kenya Institute for Public Policy Research and Analysis (KIPPRA), the Kenya National Bureau of Statistics (KNBS), and the International Food Policy Research Institute (IFPRI) under the CGIAR Initiatives on National Policies and Strategies (NPS) and Foresight, We would like to thank all funders who supported this research through their contributions to the CGIAR Trust Fund.